KAJIAN POTENSI LIGNIN UNTUK PENANGANAN LOGAM BERAT Cr (VI) (Study Of Lignin Potentials for Cr (VI) Removal) - Yuris, Yuris; Cahyani, Chandrawati; Atikah, Atikah (Jurnal Hasil Penelitian Industri, 2014)
Lignin has been isolated from black liquor with acidification by using H2SO410% on pH 2. In this condition obtained uniform precipitation and acidification avoiduneven. The lignin obtained will have similarity to functional groups of Indulin-ATstandard lignin, which is a three-dimensional polymer containing aromatic methoxylgroups, phenolic hydroxyl and aldehyde groups. Lignin has properties insoluble in waterand soluble in alkaline. Chromium (VI) is one of toxic heavy metals which is so soluble inwater that can be distributed to the aquatic environment. The purpose of this study isassessing the potential of lignin to removal of Cr(VI), while the focus of the study atdifferent pH and lignin concentration The results showed that the pH of the mixturesolution of lignin and Cr( VI ) is 2, a 25 mL of 2000 ppm lignin was able to removal to85.83% Cr(VI) from a 10 mL Cr(VI) initial concentration of 25 ppm to 1.012 ppm. Theaddition of lignin concentration at pH < 5 increase to removal of Cr(VI) due to adsorptionand coprecipitation process through occlusion mechanism, whereas at pH > 5, theaddition of lignin concentration will raise Cr(VI) removal in relatively small scale, if wecompared to pH < 5 as coprecipitation did not happen in line with lignin dissolution.